Study on the project supervision system based on the principal-agent theory - Runtong Zhang; Yang Zhou; Hongnan Zhuang; Xiaomin Zhu (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: In order to solve problems in the current project management system, the paper presents the asymmetric information games existing in construction projects through information economics viewpoints. Design/methodology/approach: The owner has private information about the project profitability and he exerts an unobservable level of effort in order to increase the feasibility of successfully completing the project in terms of meeting product specifications. The paper analyzes the principal-agent relationship between the owner and supervisor with "principal-agent theory" of the game theory. In addition, the paper validates the model through two project cases. Findings: We can conclude that the incentive contract plays an important role in reducing the moral hazard. The main contribution of this studyis to examine the influence of both pre-contractual private information and the sensitivities between the interrelated performance measures on the design of an optimal incentive contract. Social implications: At last, some advices are put forward to advance the project management system in China, and some external mechanism can effectively inhibit the"moral hazard" and "adverse selection" to occur. Originality/value: A model of principal-agent relationship between the owner and supervisor is formulated. This model takes consideration of the moral hazard, which isdifferent from most existing researches in this field.
Keywords: 650; project supervision; asymmetric information; principal-agent